2016
DOI: 10.1111/1759-7714.12400
|View full text |Cite
|
Sign up to set email alerts
|

Depleted aldehyde dehydrogenase 1A1 (ALDH1A1) reverses cisplatin resistance of human lung adenocarcinoma cell A549/DDP

Abstract: BackgroundCisplatin is the standard first‐line chemotherapeutic agent for the treatment of non‐small cell lung cancer (NSCLC). However, resistance to chemotherapy has been a major obstacle in the management of NSCLC. Aldehyde dehydrogenase 1A1 (ALDH1A1) overexpression has been observed in a variety of cancers, including lung cancer. The purpose of this study was to investigate the effect of ALDH1A1 expression on cisplatin resistance and explore the mechanism responsible.MethodsReverse transcriptase‐PCR was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
(22 reference statements)
0
20
0
Order By: Relevance
“…Recent studies have proved that ALDH1A1 is linked to drug resistance in chemotherapy [ 29 , 30 ]. With a similar role of ALDH1A1 in cancer, we also found that the inhibition of ALDH1B1 expression could increase the sensitivity of OS cells to chemotherapy (doxorubicin) (Figure 5A ), which were further supported by the inhibition abilities of colony forming and proliferation after ALDH1B1 silencing in the presence of doxorubicin (Figure 5D-5G ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have proved that ALDH1A1 is linked to drug resistance in chemotherapy [ 29 , 30 ]. With a similar role of ALDH1A1 in cancer, we also found that the inhibition of ALDH1B1 expression could increase the sensitivity of OS cells to chemotherapy (doxorubicin) (Figure 5A ), which were further supported by the inhibition abilities of colony forming and proliferation after ALDH1B1 silencing in the presence of doxorubicin (Figure 5D-5G ).…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal expression and unbalanced biological activity of ALDHs are related with a variety of disease, including alcoholic liver disease, Sjögren–Larsson syndrome, type 2 hyperprolinemia, hyperammonemia, Parkinson's disease and cancers [ 12 ]. Referring to ALDH1 subfamily, recent studies have reported that ALDH1A1 and ALDH1A3 were significantly correlated to the poor overall survival and were considered as potential prognostic markers and therapeutic targets for patients [ 22 , 23 , 29 , 30 , 35 ]. ALDH1B1 is an enzyme to compose of ALDH1, a subfamily of ALDHs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have shown that the PI3K/Akt signaling pathway is involved in multiple cellular functions, including cell proliferation, apoptosis and invasion [21][22][23]. Thus, the PI3K/Akt pathway is usually regarded as one of the key target for various tumors treatment [24][25][26], including melanoma. Calero et al indicated that the combination of the HSP90 inhibitor 17AAG with the PI3K/mTOR inhibitor NVP-BEZ235 has a synergistic activity in decreasing melanoma cell growth, inducing apoptosis and targeting simultaneously the MAPK and PI3K/Akt/mTOR pathways [27].…”
Section: Lycorine Promotes the Apoptosis Of A375 Cellsmentioning
confidence: 99%
“…It is the one of the first markers to identify HNSCC CSCs 12 . OSCC CSCs can be also isolated on the basis of functional activities of ALDH1A1, which contributes to chemotherapy resistance 13 . Recently, more and more therapies were investigated to target the CSC population.…”
Section: Introductionmentioning
confidence: 99%